2003
DOI: 10.1067/mva.2003.127
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin-based oxygen carrier HBOC-201 provides higher and faster increase in oxygen tension in skeletal muscle of anemic dogs than do stored red blood cells

Abstract: Compared with RBC transfusion, infusion of low doses of HBOC-201 maintain enhanced oxygen extraction after extended hemodilution and provide faster and higher increase in muscular tissue PO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 27 publications
3
42
1
1
Order By: Relevance
“…8 Standl et al showed preservation of skeletal muscle oxygenation in dogs. 9 Thus the data from Freitag et al 1 are consistent with observations previously made in normovolemic anemia and extends our understanding by employing a larger animal (dog) and a different HBOC (Hemopure). A common observation in all of these studies is an increase in blood pressure and in systemic vascular resistance.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…8 Standl et al showed preservation of skeletal muscle oxygenation in dogs. 9 Thus the data from Freitag et al 1 are consistent with observations previously made in normovolemic anemia and extends our understanding by employing a larger animal (dog) and a different HBOC (Hemopure). A common observation in all of these studies is an increase in blood pressure and in systemic vascular resistance.…”
supporting
confidence: 86%
“…ont montré la préser-vation de l'oxygénation des muscles squelettiques chez des chiens. 9 Les données de Freitag et coll. 1 correspondent donc aux observations faites précédemment pendant l'anémie normovolémique et elles ajoutent à nos connaissances en employant un animal plus gros, le chien, et une HBOC différente, l'Hemopure.…”
unclassified
“…Moreover, the oxygen-dissociation curve for HBOC-201 was shifted to the right relative to human hemoglobin, meaning that HBOC-201 was more able to unbind oxygen in the periphery and release it to the target organs. Standl et al [22,23] compared HBOC with autologous blood as resuscitation for dogs after massive blood loss. They found that the increase in skeletal muscle tissue oxygen tension per gram of transfused hemoglobin was higher after HBOC transfusion than after autologous RBC transfusion.…”
Section: Properties Of Hboc-201mentioning
confidence: 99%
“…Hemodynamically, increases in mean arterial pressure (MAP) and systemic vascular resistance are seen after HBOC-201 administration (18), likely through nitric oxide (NO) inhibition (12,15). Oxygen delivery to tissue has been shown to be faster and three times more efficient than human Hb (20,26). These properties, along with a lower viscosity and smaller mean diameter than a human RBC, suggest that blood substitutes may be an effective therapy in acute myocardial ischemia.…”
mentioning
confidence: 99%